Strategi Pendidikan Berlandaskan Tauhid, Amanah dan Rahmatan Lil-‘Alamin - Ifqotus Zahroh; Nur Hayati; Sukron; Syaiful Hadi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the application of the principles of tauhid, amanah, and rahmatan lil-‘alamin in strategic management practices in Islamic educational institutions. This study is motivated by the need for educational institutions to integrate Islamic values into the process of formulating, implementing, and evaluating strategies, so as to produce more humane, ethical, and sustainability-oriented governance. This study uses a descriptive qualitative approach with a literature study method, sourced from scientific articles, SINTA journals, books, and related academic documents, totaling 15 main references. Data was collected through documentation techniques, then analyzed using content analysis through the stages of data reduction, categorization, concept synthesis, and conclusion drawing. The results of the study show that the principle of tauhid is the ontological foundation that places all managerial activities as a form of devotion to Allah. The value of amanah serves as an ethical guideline in resource management, transparency, and organizational strategy accountability. Meanwhile, the value of rahmatan lil-‘alamin guides educational institutions to create strategies that are inclusive, bring benefits, and are oriented towards serving all stakeholders. The integration of these three principles produces a strategic management model that not only focuses on the effectiveness of the institution, but also strengthens character and spirituality. and social sustainability.